4 Bases Smart Bed Prototype With Multiple Load Sensing To Control The Slope Of Multiple Bases Using Servo Motor - Seder, Reyad R.M; , Dedi Ari Prasetya,ST (2017)
The focus of this paper is to create an intelligent system that allows the use and development of a bed prototype to change the outlook received into the sleeping bed, as this system can improve the perspective used in the regular bed or even the hospital user at present time, where it allows the movement of a limited number of limbs only, while it does not help patients or nurses to change the sleeping position of the patient, which will affect un the physical and vital healthy, so that prototype bed system was established to move the whole body to simplify movement, which facilitates the work of nurses and the patient to reduce the percentage of ulcers the result of long sleep in one position. The proposed platform collects information from various sensors incorporated into the bed, analyzes the data to create a time-stamped, whole-bed weight distribution map, and commands the bed's actuators to periodically adjust its surface profile to redistribute pressure over the entire body. These capabilities are combined to a form cognitive support system, for proof of concept, we have implemented algorithms and architectures that cover four key aspects of this platform: 1) data collection, 2) modeling & profiling, 3) a smart machine, and 4) acting. In this prototype the essence of making a system more smarter, by how to control the adjustment of servo motor to make the changes in the bed surface either manually or automatically, where the value that came from the load cell it will be used to defined the degree of servo in the Arduino program, on one hand to use the manual control will be commanded by re adjusting the potentiometer from (0 to 90)degree, On the other hand coupling the reading of load cell with the degrees of servo motor to control the base that mean the data came from the load cell will be used with the adjustment of base slope. Moreover it will be use a four bases of acrylic, to distribute the entire body on the surface, for measure and show how the sensor and actuator works, as well to give the best reaction to the automatic system and the most attention to the patient for any detection, because every position on the top of the surface will be followed with deferent reaction, while that the LCD keep monitoring each load cell used and each measurement of each part.